The phanerozoic carbon cycle : CO₂ and O₂ - Berner, Robert A., 1935- (OUP E-Books., 2004)
The Pharnerozoic Carbon Cycle applies an earth system science approach to the study of the long-term carbon cycle, which involves the transfer of carbon between rocks and the atmosphere, oceans and life. Theoretical modeling is used to calculate how levels of atmosphere CO2 nad O2 have changed over the past 550 million years.